Capsid Allosteric Modulators Enhance the Innate Immune Response in Hepatitis B Virus–Infected Hepatocytes During Interferon Administration. Issue 2 (25th August 2021) - Fukutomi, Keisuke; Hikita, Hayato; Murai, Kazuhiro; Nakabori, Tasuku; Shimoda, Akiyoshi; Fukuoka, Makoto; Yamai, Takuo; Higuchi, Yuichiro; Miyakawa, Kei; Suemizu, Hiroshi; Ryo, Akihide; Yamada, Ryoko; et al.
Abstract : Capsid allosteric modulators (CAMs) inhibit the encapsidation of hepatitis B virus (HBV) pregenomic RNA (pgRNA), which contains a pathogen‐associated molecular pattern motif. However, the effect of CAMs on the innate immune response of HBV‐infected hepatocytes remains unclear, and we examined this effect in this study. Administration of a CAM compound, BAY41‐4109 (BAY41), to HBV‐infected primary human hepatocytes (PHHs) did not change the total cytoplasmic pgRNA levels but significantly reduced intracapsid pgRNA levels, suggesting that BAY41 increased extracapsid pgRNA levels in the cytoplasm. BAY41 alone did not change the intracellular interferon (IFN)–stimulated gene (ISG) expression levels. However, BAY41 enhanced antiviral ISG induction by IFN‐α in HBV‐infected PHHs but did not change ISG induction by IFN‐α in uninfected PHHs. Compared with BAY41 or IFN‐α alone, coadministration of BAY41 and IFN‐α significantly suppressed extracellular HBV‐DNA levels. HBV‐infected human liver–chimeric mice were treated with vehicle, BAY41, pegylated IFN‐α (pegIFN‐α), or BAY41 and pegIFN‐α together. Compared with the vehicle control, pegIFN‐α highly up‐regulated intrahepatic ISG expression levels, but BAY41 alone did not change these levels. The combination of BAY41 and pegIFN‐α further enhanced intrahepatic antiviral ISG expression, which was up‐regulated by pegIFNα. The serum HBV‐DNA levels in mice treated with the combination of BAY41 and pegIFN‐α were the lowest observed in all the groups. Conclusion: CAMs enhance the host IFN response when combined with exogenous IFN‐α, likely due to increased cytoplasmic extracapsid pgRNA. Abstract :